(untitled) (Architecture Image Studies, 2025)
This study examined the overall impact of physical activity on the social skills of individuals with disabilities and investigated the moderating influence of associated variables. A meta-analysis was conducted based on 18 empirical studies selected according to the PICOS framework outlined in the PRISMA guidelines. The findings are as follows: First, physical activity demonstrated a moderate overall effect size on the enhancement of social skills in individuals with disabilities (ES = 0.87). Second, the heterogeneity of the overall effect size was moderate (I² = 64.9%, Q = 105.32, df = 37, p < .10). Third, moderator analysis identified the number of intervention sessions and the type of intervention as significant factors contributing to the observed heterogeneity. Fourth, an assessment of publication bias revealed minimal bias, supporting the robustness of the findings. Taken together, these results suggest that participation in more than 30 sessions of multi-component physical activity interventions may lead to the most substantial improvements in the social skills of individuals with disabilities.